Phosphorus-based polymeric scale inhibitors for energy and water industries: Synthesis, inhibition mechanism, and field deployment - Shaohua Chen; Jian Hou; Chang Da; Tao Chen (Desalination, 2026)

Physiological and molecular mechanisms of blue light-regulated archeospore formation in Pyropia yezoensis - Li-Fei Yang; Yue-Ting Pan; Hong-Chang Ding; Da-Hai Gao (Aquaculture, 2026)

MXene and silver intercalated graphene oxide membrane with antibacterial performance for high-permeability micro/nanoplastics removal - Keqin Mi; Da Chang; Liangliang Zhang; Junli Lv; Yijia Liu; Mengmeng Cheng; Shifeng Hou (Journal of Environmental Chemical Engineering, 2026)

Mainshock-aftershock fragility and risk analysis for RC frame structures based on Bayesian networks - Chang Liu; Da-Gang Lu (Engineering Structures, 2026)

Continental crustal growth in collisional orogens: Insights from the Triassic granitoids in East Kunlun, NW China - Wen-Jia Wang; Xiao-Wei Li; Yang-Ming Hu; Yong Zhang; Shuang Dai; Da-Ming Zhang; Dong-Bao Guo; Chang-Hai Luo; Juan Shen; Cheng-Yong Wang; Wei-Ming Ma (Lithos, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Poly(lactic-co-glycolic acid) (PLGA)-based vaccine delivery systems for fish: physicochemical properties, immunological mechanisms, and applications - Shu-Chun Chuang; Yi-Chen Lin; Ya-Shuan Chou; Shang-Pin Liu; Shao-Wen Hung; Ti-Chun Chang; Chung-Hwan Chen; Chung-Da Yang (Fish & Shellfish Immunology, 2026)

Evaluating the flight capacity of Callipogon relictus Semenov (Coleoptera: Cerambycidae) via flight mill and radio tracking - Jun-Young Kang; Moo-Sung Kim; Da Jeong Son; A Young Kim; Il-Kwon Kim; Chang-Jun Kim (Journal of Insect Conservation, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Maximizing methane production from food waste: Exploring through integrating Meta-analysis and machine learning - Yingnan Li; Chao Song; Chengning Wang; Da Chen; Chang Chen; Guangqing Liu (Biomass and Bioenergy, 2026)

Seismic behavior of precast concrete beam-column joints with an innovative non-porous grouted sleeve connection - Hong Chang; Yi Yuan; Guanda Liu; Da Xu; Renwei Ma (Bulletin of Earthquake Engineering, 2026)

New grylloblattid insect from the Lower Triassic Kayitou Formation of Yunnan Province, Southwest China - Shi-Xue Hu; Jin-Yuan Huang; Qi-Yue Zhang; Chang-Yong Zhou; Wen Wen; Xiao Min; Da-Ran Zheng; Qian-Qi Zhang (Palaeoworld, 2026)

Lactoferrin-derived hydrophobic peptide YIYT alleviates osteoporosis via synergistic activation of Wnt/β-catenin and BMP/Smad pathways - Zhihui Chang; Da Hong; Xiaoyu Ma; Baifeng Fu; Shuzhen Cheng; Ming Du (Food Bioscience, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Co-infection of feline coronavirus with feline parvovirus alters plaque phenotypes and single-nucleotide-variant frequencies compared with single infection in CRFK cells - Ha Yeon Kim; Van Thi Lo; Seong Sik Jang; Min Chan Kim; Alain Chrysler Chamfort; Da Young Mun; Min Chang Kang; Han Byul Lee; Dae Gwin Jeong; Hyoung Joon Moon; Hye Kwon Kim (Toxicology and Environmental Health Sciences, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Ultrasonic-vacuum combined effects on Antarctic krill oil oxidation stability: Potential mechanisms of oxygen reduction and influence on reverse micelle - Xue-Chen Pei; Fa-Wen Yin; Chang-Qiang Leng; Xin-Miao Wang; Qian Wang; Hui-Lin Liu; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2026)

Experimental and analytical investigation on continuous two-span RC beams flexural strengthened with aluminum alloy bars - Xu Chen; Guohua Xing; Yakun Li; Jun Zhang; Da Luo; Zhaoqun Chang; Boquan Liu; Haonan Wang (Engineering Structures, 2026)

Effective production of biosyngas from biomethane over spatially confined Ni catalyst with captured CO2 - Su-Ji Kim; Yeon Jeong Yu; Sung-Bin Choi; Gwan-Joong Park; Da-Bin Kang; Byung Sun Yoon; Ye-Eun Jeon; Min-Young Kim; Jeong-Chul Kim; Young-Kwon Park; Chang Hyun Ko (Bioresource Technology, 2026)

Distribution and correlation of trace elements in Eurasian otters (Lutra lutra) from South Korea - Da Sol Park; Eun Jae Park; Dahye Shin; Rihyun Kim; Bongkyun Kim; Yongsun Hyun; Hee-Jong Kim; Kyu-Vin Kim; Chang Uk Chung; Dong-Hyuk Jeong; Jong Seung Kim; Ju Yeong Park; et al. (Environmental Science and Pollution Research, 2026)

E-cigarette vapor alters gut microbiota composition in zebrafish - Thi Ngoc Mai Dong; Delbert Almerick T. Boncan; Carl Andersen Macaraeg Tan; Da-Wei Liu; Hsin-Yu Sun; Ting-Wei Huang; Chen Hsu; Kuo-Chang Chu; Zulvikar Syambani Ulhaq; Keng Po Lai; Douglas Robert Drummond; Yukiko Ogino; et al. (Science of The Total Environment, 2026)

Melatonin regulates petal senescence in peony (Paeonia lactiflora Pall.) cut flowers via the ROS pathway - Yuxuan Wang; Miao Sun; Mengdi Wang; Xiaolong Lv; Wei Zhu; Le Chen; Xi Chen; Chang Guo; Jaime A. Teixeira da Silva; Xiaonan Yu (Postharvest Biology and Technology, 2026)

Quantitative prediction of fracture distribution in deep conglomerate reservoirs of the Bozhong 19-6 South structure, offshore Bohai Bay Basin, East China: Insights from numerical simulation of multiphase strike-slip regimes - Liang Zhou; Chao Deng; Li-ya Da; Yu Xia; He-wei Hu; Kai Ji; Chang-yu Fan; Yong Cheng; Yu-jie Ning; Xiao-fang Yang (Marine and Petroleum Geology, 2026)

Bacteriophage emulsion for prevention of Salmonella contamination in eggshells - Su Jin Jo; Sang Guen Kim; Sib Sankar Giri; Sung Bin Lee; Jae Hong Park; Mae Hyun Hwang; Da Sol Park; Eun Jae Park; Se Chang Park (International Journal of Food Microbiology, 2026)

Study on browning mechanism of Antarctic krill meal during storage: based on the model system approach - Chao Guo; Xiang-Bo Zeng; Chang-Qiang Leng; De-Yang Li; Qian Wang; Fa-Wen Yin; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2026)

Effect of papaya leaf extract on growth performance, skin mucosal immune responses, liver enzymes, disease resistance, and tight junctions of Cyprinus carpio - Sib Sankar Giri; Jin Woo Jun; Sung Bin Lee; Su Jin Joo; Mae Hyun Hwang; Jae Hong Park; Da Sol Park; Eun Jae Park; Venkatachalam Sukumaran; Se Chang Park (Fish & Shellfish Immunology, 2026)

Scalable metallic-electron donation systems for optimized glycerol-to-1,3-propanediol bioconversion - Da Seul Kong; Sakuntala Mutyala; Himanshu Khandelwal; Minsoo Kim; Shuwei Li; Chang Dou; Jung Rae Kim; Changman Kim (Chemical Engineering Journal, 2026)

Geographical effects on ambient air pollution and clinical visits for respiratory diseases: a case study with three exposure scenarios - Hui-Ju Wen; Shu-Li Wang; Chih-Da Wu; Mao-Chang Liang (Atmospheric Pollution Research, 2026)

Mantle heterogeneity and complicated melt migration revealed by chemical gradients across the dunite-harzburgite sequence in the Zedong ophiolite, South Tibet - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Tong Liu; Chang Zhang; Bo-Da Liu (Contributions to Mineralogy and Petrology, 2026)

Detection of H9N2 Avian Influenza Virus in commercial raw meat-based diets for dogs and cats in South Korea - Chang-Tae Kim; Dong-Wook Lee; Da-Won Kim; Ji-Yun Kim; Ye-Jin Lee; Hee-Su Kim; Seulgi Bae; Jung-Hoon Kwon (Veterinary Microbiology, 2025)

Decaprenyl diphosphate synthases in Monolepta hieroglyphica: DPPS-mediated CoQ biosynthesis impacts juvenile hormone and gut microbiota - Xuan Song; Jun-feng Kou; Chang Liu; Yong Yang; Da-wei Zhang; Chao-qun Yi; Wen-tao Liu; Run Chen; Wei-hao Guo; Yue-qin Wang; Tian-tao Zhang; Yong-jun Zhang (Insect Biochemistry and Molecular Biology, 2025)

Vacuum freeze drying driven by photovoltaic power generation used as a green pretreatment methodology to enhance enzymatic conversion of rice straw for poly(3-hydroxybutyrate) production by Cupriavidus necator - Youwei Zhang; Wen-Chang Chang; Da-Wei Huang; Heng Chi; Zhongxuan Gou; Tingting Li (Bioresource Technology Reports, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

A radiomics-driven machine learning model for predicting bladder cancer prognosis identifies genes associated with radiomic features - Xin Chang Zou; Bin Wang; Zhan Jiang Yu; Hai Chao Chao; Xiang Da Xu; Tao Zeng (Clinical & Experimental Metastasis, 2025)

Effect of Illicium verum Hook.f. (star anise) extract on the modulation of systemic and mucosal immunity in Aeromonas hydrophila-aggravated Cyprinus carpio - Sib Sankar Giri; Hyoun Joong Kim; Subrata Saha; Jae Hong Park; Sung Bin Lee; Su Jin Joo; Mae Hyun Hwang; Da Sol Park; Eun Jae Park; Kihae Ra; Sukumaran Venkatachalam; Se Chang Park (Fish & Shellfish Immunology, 2025)

Automatic quantification, grading and five-year prediction of myopic fundus tessellation: a multi-center, longitudinal deep learning study - Wen-Da Zhou; Li Dong; Wen-Xue Li; Li-Jian Fang; Tong Ma; Lie Ju; Zhao-Hui Wang; Yuan Luo; Wanli Miles Zhang; Xian-Gang Chang; Zong-Yuan Ge; Jost. B. Jonas; et al. (Science China Life Sciences, 2025)

A two-stage multi-step-ahead Gated-Recurrent-Unit-based method with the use of sewer level data for improving real-time forecasting of inundation depth - Song-Yue Yang; You-Da Jhong; Bing-Chen Jhong; Ling Fan-Chiang; Ming-Chang Tsai (Journal of Hydrology, 2025)

Revealing greenhouse gas emissions variability in industrial wastewater treatment: A plant-level study of CH4 and N2O emission factors - Duyen Phuc-Hanh Tran; Da-Wei Tsai; Tien-Chin Chang; Ya-Fen Wang; Sheng-Jie You (Journal of Environmental Chemical Engineering, 2025)

Whole genome sequencing reveals telomere associated genomic differences between healthy and unhealthy aging in a Korean population - Ji-Hye Oh; Hyo Jeong Lee; Wonkyung Kim; Da Eun Oh; Hong-Kyu Kim; Eun Hee Kim; Jaewon Choe; Ha Ra Jun; Chae Won Park; Young Gwang Kang; Chong Jai Kim; Chang Ohk Sung; et al. (Biogerontology, 2025)

Comparative impacts of fragmented versus spherical microplastics on the marine rotifer Brachionus koreanus: Multigenerational chronic toxicity and multi-omics perspective - Je-Won Yoo; Tae-June Choi; Jong-Seok Park; Youn-Ha Lee; Da Hyeon Hwang; Chang-Bae Kim; Tae-Yong Jeong; Young-Mi Lee (Journal of Hazardous Materials, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Alleviation of LPS-induced oxidative stress and inflammation by lesbicoumestan (7) via the increase of Nrf2 expression in mouse Kupffer cells - Xiangying Li; Lulu Yao; Young-Chang Cho; Da Young Lee; Namki Cho; Guijae Yoo; Sang Yoon Choi; Somy Yoon; Jae Sung Lim (Toxicology and Applied Pharmacology, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

Value-added utilization of vegetable waste for the production of caproate through carbon chain elongation - Da Chen; Chao Song; Xiaochuang Zhang; Chang Chen; Guangqing Liu (Food and Bioproducts Processing, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Regional transport characteristics of PM2.5 pollution events in Beijing during 2018–2021 - Dejia Yin; Qian Song; Yuanxi Guo; Yueqi Jiang; Zhaoxin Dong; Bin Zhao; Shuxiao Wang; Da Gao; Xing Chang; Haotian Zheng; Shengyue Li; Yunting Li; et al. (Journal of Environmental Sciences, 2025)

Addressing plastic pollution: A 3D-printed porous PAC scaffold for effective nanoplastic removal - Namyeon Kim; Da-Yeon Kim; Yunsoo Chang; Eui-Man Jung; Seung-Woo Lee; Eun-Hee Lee (Chemosphere, 2025)

Large-scale patterns and drivers of soil organic nitrogen depolymerization - Yuanrui Peng; Tao Wang; Wolfgang Wanek; Dexin Gao; Da Wei; Ruiying Chang (Soil Biology and Biochemistry, 2025)

Corrigendum to “Controlled atmosphere storage enhances Korean melon shelf life and quality: A comparative metabolic analysis with reefer container export” [Postharvest Biol. Technol. 219, January 2025, 113238] - Woochul Ju; Ji-Hyun Lee; Eunsu Do; Da-yeong Ko; Eungu Jee; Min-Sun Chang; Hyang Lan Eum; Haejo Yang; Kang-Mo Ku (Postharvest Biology and Technology, 2025)

Innovating Taiwan's greenhouse gas estimation: A case study of atmospheric methane using GeoAI-Based ensemble mixed spatial prediction model - Hao-Ting Chang; Yinq-Rong Chern; Aji Kusumaning Asri; Wan-Yu Liu; Chin-Yu Hsu; Ta-Chih Hsiao; Kai Hsien Chi; Shih-Chun Candice Lung; Chih-Da Wu (Journal of Environmental Management, 2025)

Enhanced nonradical oxidation of thiocyanate by nano γ-Fe2O3 and Fe3C-modified 2D hierarchical porous carbon nanosheets - Yang Yang; Jianshe Chen; Daxue Fu; Yongfeng Chang; Kuiren Liu; Shuang Cui; Yina Li; Binchuan Li; Shicheng Wei; Da Li; Qing Han (Journal of Environmental Chemical Engineering, 2025)

Ferric ammonium citrate regulates iron death in mature porcine oocytes and their embryonic development in vitro through the NRF2 signaling pathway - Da Xu; Caifei Li; Yao Huang; Kaixin Hu; Cheng Wang; Pengyang Zhou; Haiying Shen; Chang Liu; Jiatong Xu; Jinyuan He; Jiaxu Jiang; Qi Qi; et al. (Theriogenology, 2025)

Controlled atmosphere storage enhances Korean melon shelf life and quality: A comparative metabolic analysis with reefer container export - Woochul Ju; Ji-Hyun Lee; Eunsu Do; Da-yeong Ko; Eungu Jee; Min-Sun Chang; Hyang Lan Eum; Haejo Yang; Kang-Mo Ku (Postharvest Biology and Technology, 2025)

Bond-slip behavior of Aluminum Alloy (AA) bars for near-surface mounted (NSM) technique - Xu Chen; Guohua Xing; Da Luo; Yongjian Lu; Zhaoqun Chang; Enrique del Rey Castillo; Jason Ingham (Engineering Structures, 2025)

Critical considerations for co-administering rivaroxaban and vonoprazan: Unveiling potential pharmacokinetic interactions - Xiao-yu Xu; Zhe-yan Zhang; Xiao-dan Zhang; Jian-chao Luo; Yun-shan Zhong; Le-hao Jin; Da-peng Dai; Jian-chang Qian (Chemico-Biological Interactions, 2025)

Remediation of heavy metal contaminated soil in mining areas with vaterite-type biological calcium carbonate - Jun-li Chen; Chang-xiong Zou; Wei-da Wang; Chun-li Zheng; Qing-hong Jiang; Zhe Wang (Process Safety and Environmental Protection, 2024)

Constraints of upper crust magmatic processes on the formation of Saindak porphyry Cu deposit: Insights from mineral geochemistry - Lu Wang; Zi-xuan Wang; Yuan-chuan Zheng; Zeng-qian Hou; Zhu-sen Yang; Chang-da Wu; Xin Li (Lithos, 2024)

Two factors facilitate the cost-effective and harmless cementation of rare earth slags through MICP technology: Carbonic anhydrase bacteria and endogenous calcium ions - Wei-da Wang; Chang-xiong Zou; Tan Wang; Bei Wang; Ming-tao Zhu; Wan-qi Zhang; Ling Zhao; Zhe Wang; Zhao-yu Wang (Journal of Environmental Chemical Engineering, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

Clinical impact of major pathogenic genotypes of Pseudomonas aeruginosa associated with refractory chronic suppurative otitis media - Chang Hyeon Lee; Kyu-Min Kim; Jeong-Ih Shin; Da Min Jeong; Jung-Hyun Byun; Myung Hwan Jung; Hyung-Lyun Kang; Kee Woong Kwon; Seung Chul Baik; Woo-Kon Lee; Seong-Ki Ahn; Chae Dong Yim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Comparative analysis of the transcriptomes from regenerated plants and root explants of endangered Oplopanax elatus - Ji Won Seo; Hong Ju Choi; Da Ye Ham; Jiu Park; Ik Young Choi; Chang Yeon Yu; Myong Jo Kim; Eun Soo Seong (Genes & Genomics, 2024)

Petrogenesis of the pyroxenitic Moho transition zone in the Zedong ophiolite, Southeastern Tibet - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Liang-Liang Zhang; Chang Zhang; Tong Liu; Bo-Da Liu; Wei-Qi Zhang; Yin-Zheng Lin; Wen-Bin Ji (Lithos, 2024)

Efficient multi-objective optimization and operational analysis of amine scrubbing CO2 capture process with artificial neural network - Yu-Da Hsiao; Chuei-Tin Chang (International Journal of Greenhouse Gas Control, 2024)

A novel water electrolysis hydrogen production system powered by a renewable hydrovoltaic power generator - Seung-Hwan Lee; Yongbum Kwon; Sungsoon Kim; Jeungjai Yun; Eugene Kim; Gyuyong Jang; Yoseb Song; Bum Sung Kim; Chang-Suk Oh; Yong-Ho Choa; Jae-Yup Kim; Jong Hyeok Park; et al. (Chemical Engineering Journal, 2024)

Association of Asian dust storms and PM2.5 with clinical visits for respiratory diseases in children - Hui-Ju Wen; Shu-Li Wang; Chih-Da Wu; Mao-Chang Liang (Atmospheric Environment, 2024)

Status and trends in the stability of the three largest ice shelves in Antarctica - Rongxing Li; Guojun Li; Lu An; Menglian Xia; Da Lv; Yuan Cheng; Aiguo Zhao; Tian Chang; Xiangbin Cui; Shengkai Zhang; Shijie Liu; Yixiang Tian; et al. (Science China Earth Sciences, 2024)

Objectives and achievements of the HUMN project on its 26th anniversary - Michael Fenech; Nina Holland; Errol Zeiger; Peter Wushou Chang; Micheline Kirsch-Volders; Claudia Bolognesi; Helga Stopper; Lisbeth E. Knudsen; Siegfried Knasmueller; Armen Nersesyan; Philip Thomas; Varinderpal Dhillon; et al. (Mutation Research - Reviews in Mutation Research, 2024)

Newly graphene/polypyrrole (rGO/PPy) modified carbon felt as bio-cathode in bio-electrochemical systems (BESs) achieving complete denitrification - Yue-Jia Yang; Shuai Wang; Da Kang; Xin Lu; Zi-Chang Lu; Zhuo-Chao Liu; Li-Ming Yang; Dan Cui (Environmental Research, 2024)

The effect of extracellular polymeric substances on MICP solidifying rare earth slags and stabilizing Th and U - Chang-xiong Zou; Zhen-bo Sun; Wei-da Wang; Tan Wang; Yan-xin Bo; Zhe Wang; Chun-li Zheng (World Journal of Microbiology and Biotechnology, 2024)

Soil water potential measurement using fiber-optic sensing technique - Jin-Jian Xu; Chao-Sheng Tang; Qing Cheng; Farshid Vahedifard; Da-Zhan Zhang; Chang Sun; Bin Shi (Journal of Hydrology, 2024)

Ambient volatile organic compounds in the Seoul metropolitan area of South Korea: Chemical reactivity, risks and source apportionment - Da-Mee Eun; Yun-Sung Han; Ilkwon Nam; YuWoon Chang; Sepyo Lee; Jeong-Hoo Park; Sung Yong Gong; Jong-Sang Youn (Environmental Research, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

The formation mechanism of low-angle loess-mudstone seismic landslides - Da Peng; Jingshan Bo; Wenhao Qi; Chaoyu Chang; Xiaobo Li; Yushi Duan (Soil Dynamics and Earthquake Engineering, 2024)

Corrigendum to “Effects of blue space exposure in urban and natural environments on psychological and physiological responses: A within-subject experiment” [Urban For. Urban Green. 87 (2023) 1–9/128066] - Jie Yin; Jittakon Ramanpong; Jin Chang; Chih-Da Wu; Pei-Hua Chao; Chia-Pin Yu (Urban Forestry & Urban Greening, 2024)

Heterologous expression of taxane genes confers resistance to fall armyworm in Nicotiana benthamiana - Zhenlu Xu; Yaohua Zhai; Huimin Chang; Da Yan; Pengliang Ge; Guangming Ren; Lijun Zhang; Ye Yuan; Ruoyan Wang; Wentao Li; Fuguang Li; Maozhi Ren; et al. (Plant Cell Reports, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Do greenness and landscape indices for greenspace correlate with suicide ratio? - Hsiao-Yun Lee; Hao-Ting Chang; Samuel Herianto; Chi-Shin Wu; Wan-Yu Liu; Chia-Pin Yu; Wen-Chi Pan; Chih-Da Wu (Landscape and Urban Planning, 2024)

Optimization of LSTM Parameters for Flash Flood Forecasting Using Genetic Algorithm - You-Da Jhong; Chang-Shian Chen; Bing-Chen Jhong; Cheng-Han Tsai; Song-Yue Yang (Water Resources Management, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

Properties and mechanisms of steel slag strengthening microbial cementation of cyanide tailings - Chang-xiong Zou; Meng Xiao; Qing-hong Jiang; Zhe Wang; Chun-li Zheng; Wei-da Wang (Chemosphere, 2024)

The therapeutic efficacy of silver loaded rhenium disulfide nanoparticles as a photothermal agent for cancer eradication - Sesha Subramanian Murugan; Won Hur; Seong Eun Son; Han Been Lee; Chang Hyeon Ha; Su Jeong Lee; Se Hwa Cheon; Do Hyeon Kim; Sung Min Jeon; Da Young Choi; Jayachandran Venkatesan; Gi Hun Seong (Journal of Photochemistry and Photobiology B: Biology, 2024)

Biosynthesis of l-histidine from marine biomass-derived galactans in metabolically engineered Corynebacterium glutamicum - Minhye Kim; Jun Won Oh; Da Woon Jeong; Byeong-Hyeon Cho; Joonhee Chang; Xiaoyu Shi; Sung Ok Han (Bioresource Technology, 2024)

The effect of different LED wavelengths on the components and biosynthesis of isoflavonoid in sprout Astragalus membranaceus - Ji Won Seo; Da Ye Ham; Jae Geun Lee; Myong Jo Kim; Chang Yeon Yu; Eun Soo Seong (Protoplasma, 2024)

Dihydrotanshinone I reduces H9c2 cell damage by regulating AKT and MAPK signaling pathways - Ya-chao Wang; Yi-da Shao; Chang-le Shao; Xiao-qi Guan; Ping-ping Lu; Ke Ning; Bao-nian Liu; Hai-dong Guo (In Vitro Cellular & Developmental Biology - Animal, 2024)

Feeding ecology of Antarctic toothfish, Dissostichus mawsoni in the subarea 88.3 (Bellingshausen Sea and eastern Amundsen Sea) of the Southern Ocean - Gi Chang Seong; Sangdeok Chung; Do-Gyun Kim; Da Yeon Kang; Suyeon Jin; Gun Wook Baeck (Frontiers in Marine Science, 2023)
Understanding feeding ecology is essential for ecosystem-based management. As dietary data can show differences depending on the spatiotemporal and ontogenetic aspects of the sample, the results should be derived based on various size classes and samples over a wide spatiotemporal range. Morphological analysis of the stomach contents of Dissostichus mawsoni , a piscivore, collected at depths of 603–2,113 m in subarea 88.3 during the Antarctic summer fishing seasons from 2016 to 2020 was used to assess the dietary composition according to the research block, fishing season, depth, and size. Here, we used 1,639 D. mawsoni specimens with a total length range of 44.5–189.0 cm. The dietary composition of D. mawsoni did not show significant differences by fishing season but differed with research block, depth, and size. Macrouridae dominated research blocks 88.3_1 and 88.3_3; Nototheniidae dominated research blocks 88.3_2 and 88.3_6; and Channichthyidae dominated research blocks 88.3_4 and 88.3_5. The proportion of Nototheniidae decreased as depth increased, whereas the consumption of Channichthyidae increased gradually with depth in research blocks 88.3_3 and 88.3_4. The proportion of Channichthyidae decreased as body size increased, whereas the consumption of Macrouridae increased gradually with body size in both blocks 88.3_3 and 88.3_4. During the study period, the dietary composition of D. mawsoni in both blocks 88.3_3 and 88.3_4 did not show significant temporal differences, suggesting that these data could be used as a baseline for identifying future environmental changes in the region. This study provides information on the relationships between various species and benthic fish fauna, which are essential for ecosystem-based management.

Folic Acid and Folinic Acid Protect Hearts of Aging Triple-transgenic Alzheimer’s Disease mice via IGF1R/PI3K/AKT and SIRT1/AMPK Pathways - Da-Tong Ju; Rwei-Fen S. Huang; Bruce Chi-Kang Tsai; Yi-Chen Su; Ping-Ling Chiu; Yung-Ming Chang; V. Vijaya Padma; Tsung-Jung Ho; Chun-Hsu Yao; Wei-Wen Kuo; Chih-Yang Huang (Neurotoxicity Research, 2023)

Pyroxenite–harzburgite sequences in the Dazhuqu ophiolite (Southern Tibet) formed through hydrous melt infiltration and melt–peridotite reaction - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Tong Liu; Chang Zhang; Bo-Da Liu; Yin-Zheng Lin; Wei-Qi Zhang; Wen-Bin Ji (Contributions to Mineralogy and Petrology, 2023)

Solidification treatment of rare earth tailings by a renewable biological cementation method - Wei-da Wang; Tan Wang; Zhen-bo Sun; Yan-xin Bo; Chang-xiong Zou; Zhe Wang; Chun-li Zheng (Process Safety and Environmental Protection, 2023)

Efficient chemo-catalytic transformation of spent coffee grounds into lactic acid using erbium triflate - Geon-Soo Ha; Ho Seung Song; Da Hae Oh; Mark Mba-Wright; Jeong-Myeong Ha; Chun-Jae Yoo; Jae-Wook Choi; Chang Soo Kim; Byong-Hun Jeon; Hanseob Jeong; Kwang Ho Kim (Journal of Environmental Chemical Engineering, 2023)

Construction of a novel ferrihydrite/MoS2 heterogeneous Fenton-like catalyst for efficient degradation of organic pollutants under neutral conditions - Da Chang; Juanjuan Sun; Chang Wang; Linlin Hao; Ming Zeng (Environmental Science and Pollution Research, 2023)

Effects of blue space exposure in urban and natural environments on psychological and physiological responses: A within-subject experiment - Jie Yin; Jittakon Ramanpong; Jin Chang; Chih-Da Wu; Pei-Hua Chao; Chia-Pin Yu (Urban Forestry & Urban Greening, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

High quality diet attenuated the positive association between polychlorinated biphenyls and premature mortality among middle-aged and older adults - Weigui Ni; Qingping Xue; Shanshan Zhang; Xue Yang; Shiyi Wu; Xingchen He; Yan Xiao; Wenling Chang; Ying Wen; Yichao Huang; Yi-Xin Wang; Da Chen; et al. (Environmental Research, 2023)

Petrogenesis of Sn-related granitoids and implications for the formation of the world-class Gejiu Sn district, South China: Insights from whole-rock and accessory mineral geochemistry - Xin Li; Yuan-chuan Zheng; Yang Shen; Chang-da Wu; Pei-yan Xu; Yan-shen Yang; Lu Wang; Zeng-qian Hou (Lithos, 2023)

Determination of potential sources of heavy metals in patients with urothelial carcinoma in central Taiwan: a biomonitoring case–control study - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Chih-Da Wu; Chiu-Shong Liu; Mu-Chi Chung; Hui-Tsung Hsu (Environmental Geochemistry and Health, 2023)

Removal of heavy metals using Iris species: A potential approach for reclamation of heavy metal-polluted sites and environmental beautification - Aung Htay Naing; Da Young Park; Hyeong Cheol Park; Chang Kil Kim (Environmental Science and Pollution Research, 2023)

Competitive adsorption of heavy metals between Ca–P and Mg–P products from wastewater during struvite crystallization - Yazhou Wang; Jinrong Da; Yuxuan Deng; Rui Wang; Xiaoning Liu; Jianbo Chang (Journal of Environmental Management, 2023)

Effect of extracellular polymers in the wastewater on the incorporation of heavy metals with struvite and their adsorption mechanism - Yazhou Wang; Liya Ma; Jinrong Da; Yan Liang; Xiaoning Liu; Jianbo Chang (Journal of Environmental Chemical Engineering, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Capacitively coupled effect and capacitive decoupling of multichannel controlled-source audio magnetotellurics observations - Da Lei; Qi-hui Zhen; Ruo Wang; Chang-min Fu; Hao Ren (Applied Geophysics, 2023)

Effects of by-products from producing yacon (Smallanthus sonchifolius) juice as feed additive on growth performance, digestive enzyme activity, antioxidant status, related gene expression, and disease resistance against Streptococcus iniae in juvenile black rockfish (Sebastes schlegelii) - Hwa Yong Oh; Tae Hoon Lee; Chang-Hwan Lee; Da-Yeon Lee; Min-Young Sohn; Ryeong-Won Kwon; Jeong-Gyun Kim; Hee Sung Kim (Aquaculture, 2023)

JA-induced TaMPK6 enhanced the freeze tolerance of Arabidopsis thaliana through regulation of ICE-CBF-COR module and antioxidant enzyme system - Meng-Meng Yu; Rui Wang; Jing-Qiu Xia; Chang Li; Qing-Hua Xu; Jing Cang; Yu-Ying Wang; Da Zhang (Plant Science, 2023)

Ultrapotassic enclaves in the Miocene adakitic granitoids, southern Tibet: Direct evidence for collision-related crust-mantle interaction and its implications - Chang-da Wu; Yuan-chuan Zheng; Bo Xu; Zeng-qian Hou; Peng Chai; Xin Li; Lin-yuan Zhang; Zi-xuan Wang; Lu Wang; Yang Shen (Lithos, 2023)

Insight into the mechanism of gasification fine slag enhanced flotation with selective dispersion flocculation - Da Shi; Jianbo Zhang; Huiquan Li; Shaopeng Li; Fayu He; Jiangshan Qu; Ruiqi Chang; Ganyu Zhu; Chennian Yang; Chenye Wang (Fuel, 2023)

Correction: Identification of extracellular vesicles from J strain and wild isolate of Mycoplasma hyopneumoniae - Luiz Fernando Lino de Souza; Glaziele Campbell; Guilherme Gabriel Souza Arthuso; Natália Fialho Gonzaga; Camilla Ribeiro Alexandrino; Viviane Sisdelli Assao; Maria Aparecida Scatamburlo Moreira; Maura Da Cunha; Yung-Fu Chang; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2023)

The involvement of an HMG-box gene in germ cell genesis in Pyropia haitanensis - Hong-Chang Ding; Long-Chen Tang; Da-Hai Gao; Xing-Hong Yan (Algal Research, 2023)

Aedes aegypti Totivirus identified in mosquitoes in the Brazilian Amazon region - Élcio Leal; Edcelha Soares D.’Athaide Ribeiro; Fred Julio Costa Monteiro; Julia Pantoja Marques; Diuliana dos Santos Mendes; Vanessa S. Morais; Emerson Luiz Lima Araújo; Ramendra Pati Pandey; Chung-Ming Chang; Xutao Deng; Eric Delwart; Antonio Charlys da Costa; et al. (Virus Genes, 2023)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

Synergy of surface modified nanoparticles and surfactant in wettability alteration of calcite at high salinity and temperature - Wenyue Tang; Pingkeng Wu; Chang Da; Shehab Alzobaidi; Justin Harris; Brooke Hallaman; Dongdong Hu; Keith P. Johnston (Fuel, 2023)

Using cluster algorithms with a machine learning technique and PMF models to quantify local-specific origins of PM2.5 and associated metals in Taiwan - Chin-Yu Hsu; Jhy-Charm Soo; Sheng-Lun Lin; Chih-Da Wu; Kai Hsien Chi; Wen-Chang Hsu; Chun-Chieh Tseng; Yu-Cheng Chen (Environmental Pollution, 2023)

ε-Poly( -lysine)-based bioreducible nanogels for mitochondria-targeted delivery and release: Hydrophobicity-tuned nucleus-to-mitochondria organelle-targeting switch and slow disulfide cleavage - Hana Cho; Yeon Su Choi; Da Gyeom Choung; Won Gu Choi; Min Seo Lee; Yong-Yeon Cho; Joo Young Lee; Hye Suk Lee; Han Chang Kang (Chemical Engineering Journal, 2023)

Regulation of reactive oxygen species on production, release, and early germination of archeospores in Pyropia yezoensis - Chao-Feng Teng; Da-Hai Gao; Hong-Chang Ding; Xing-Hong Yan (Algal Research, 2023)

Long short-term memory integrating moving average method for flood inundation depth forecasting based on observed data in urban area - Song-Yue Yang; Bing-Chen Jhong; You-Da Jhong; Tsung-Tang Tsai; Chang-Shian Chen (Natural Hazards, 2022)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Greenhouse gas emission benefits of adopting new energy vehicles in Suzhou City, China: A case study - Cui Da; Xinyu Gu; Chunchen Lu; Ruiqi Hua; Xinyue Chang; Yuanyuan Cheng; Feiyue Qian; Yiheng Wang (Environmental Science and Pollution Research, 2022)

Assessing the effective spatial characteristics of input features through physics-informed machine learning models in inundation forecasting during typhoons - Bing-Chen Jhong; Chung-Yi Lin; You-Da Jhong; Hsiang-Kuan Chang; Jung-Lien Chu; Hsi-Ting Fang (Hydrological Sciences Journal, 2022)

Real-time Neural-network-based Ensemble Typhoon Flood Forecasting Model with Self-organizing Map Cluster Analysis: A Case Study on the Wu River Basin in Taiwan - You-Da Jhong; Hsin-Ping Lin; Chang-Shian Chen; Bing-Chen Jhong (Water Resources Management, 2022)

Air pollution associated with cognitive decline by the mediating effects of sleep cycle disruption and changes in brain structure in adults - Chen-Chen Lo; Wen-Te Liu; Yueh-Hsun Lu; Dean Wu; Chih-Da Wu; Ting-Chieh Chen; Yu-Ting Fang; Yu-Chun Lo; You-Yin Chen; Lo Kang; Cheng-Yu Tsai; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Brain Reactions to Opening and Closing the Eyes: Salivary Cortisol and Functional Connectivity - Shen-Da Chang; Po-Chih Kuo; Karl Zilles; Tim Q. Duong; Simon B. Eickhoff; Andrew C. W. Huang; Arthur C. Tsai; Philip E. Cheng; Michelle Liou (Brain Topography, 2022)
This study empirically assessed the strength and duration of short-term effects induced by brain reactions to closing/opening the eyes on a few well-known resting-state networks. We also examined the association between these reactions and subjects’ cortisol levels. A total of 55 young adults underwent 8-min resting-state fMRI (rs-fMRI) scans under 4-min eyes-closed and 4-min eyes-open conditions. Saliva samples were collected from 25 of the 55 subjects before and after the fMRI sessions and assayed for cortisol levels. Our empirical results indicate that when the subjects were relaxed with their eyes closed, the effect of opening the eyes on conventional resting-state networks (e.g., default-mode, frontal-parietal, and saliency networks) lasted for roughly 60-s, during which we observed a short-term increase in activity in rs-fMRI time courses. Moreover, brain reactions to opening the eyes had a pronounced effect on time courses in the temporo-parietal lobes and limbic structures, both of which presented a prolonged decrease in activity. After controlling for demographic factors, we observed a significantly positive correlation between pre-scan cortisol levels and connectivity in the limbic structures under both conditions. Under the eyes-closed condition, the temporo-parietal lobes presented significant connectivity to limbic structures and a significantly positive correlation with pre-scan cortisol levels. Future research on rs-fMRI could consider the eyes-closed condition when probing resting-state connectivity and its neuroendocrine correlates, such as cortisol levels. It also appears that abrupt instructions to open the eyes while the subject is resting quietly with eyes closed could be used to probe brain reactivity to aversive stimuli in the ventral hippocampus and other limbic structures.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Identification of extracellular vesicles from J strain and wild isolate of Mycoplasma hyopneumoniae - Luiz Fernando Lino de Souza; Glaziele Campbell; Guilherme Gabriel Souza Arthuso; Natália Fialho Gonzaga; Camilla Ribeiro Alexandrino; Viviane Sisdelli Assao; Maria Aparecida Scatamburlo Moreira; Maura Da Cunha; Yung-Fu Chang; Abelardo Silva-Júnior (Brazilian Journal of Microbiology, 2022)

Crack propagation mechanism of single- and double-flawed rock specimens under tension–shear stress condition - Duofeng Cen; Chang Liu; Chao Liu; Da Huang (Arabian Journal of Geosciences, 2022)

High-pressure water jet for rock burst prevention of roadway ribs in strong mine pressure mines: a case study - Zeng-qiang Yang; Chang Liu; Da-wei Wang (Arabian Journal of Geosciences, 2022)

The mechanism and application of high-pressure water jet technology to prevent compound dynamic disaster - Zeng-qiang Yang; Chang Liu; Feng-shuo Li; Lin-ming Dou; Gang-wei Li; Da-wei Wang (Arabian Journal of Geosciences, 2021)

Changes in the Gene Expression Profiles of the Inferior Colliculus Following Unilateral Cochlear Ablation in Adult Rats - Hog Kwon Kil; Kyung Woon Kim; Da-hye Lee; So Min Lee; Chang Ho Lee; So Young Kim (Biochemical Genetics, 2021)

Systemic effect of dietary lipid levels and α-lipoic acid supplementation on nutritional metabolism in zebrafish (Danio rerio): focusing on the transcriptional level - Chen-cui Huang; Jian Sun; Hong Ji; Gen Kaneko; Xing-da Xie; Zhi-guang Chang; Wei Deng (Fish Physiology and Biochemistry, 2020)

Theta-burst transcranial magnetic stimulation induced functional connectivity changes between dorsolateral prefrontal cortex and default-mode-network - Yuanqi Shang; Da Chang; Jian Zhang; Wei Peng; Donghui Song; Xin Gao; Ze Wang (Brain Imaging and Behavior, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Salt tolerance and exclusion in the mangrove plant Avicennia marina in relation to root apoplastic barriers - Hao Cheng; Anifiok Inyang; Chang-Da Li; Jiao Fei; Yan-Wu Zhou; You-Shao Wang (Ecotoxicology, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Effects of long-term planting on PhytOC storage and its distribution in soil physical fractions in Moso bamboo forests in subtropical China - Chengpeng Huang; Yongchun Li; Lin Jin; Xiaoqiang Gong; Jiasen Wu; Da Dong; Scott X. Chang; Peikun Jiang (Journal of Soils and Sediments, 2020)

Dynamic Elastic Modulus and Damping Ratio of Unsaturated Red Clay - Chang-xi Huang; Xing-hua Wang; Hao Zhou; Da-chao Qin (Geotechnical and Geological Engineering, 2020)

A critical review on environmental implications, recycling strategies, and ecological remediation for mine tailings - Da-Mao Xu; Chang-Lin Zhan; Hong-Xia Liu; Han-Zhi Lin (Environmental Science and Pollution Research, 2019)

Associations of brain entropy (BEN) to cerebral blood flow and fractional amplitude of low-frequency fluctuations in the resting brain - Donghui Song; Da Chang; Jian Zhang; Qiu Ge; Yu-Feng Zang; Ze Wang (Brain Imaging and Behavior, 2019)

Antifungal activity of Annona coriacea Mart. ethanol extracts against the aetiological agents of cryptococcosis - Adriana Araújo de Almeida-Apolonio; Fabiana Gomes da Silva Dantas; Allan Belarmino Rodrigues; Claudia Andréa Lima Cardoso; Melyssa Negri; Kelly Mari Pires de Oliveira; Marilene Rodrigues Chang (Natural Product Research, 2019)

Valinomycin, produced by Streptomyces sp. S8, a key antifungal metabolite in large patch disease suppressiveness - Chang-Wook Jeon; Da-Ran Kim; Youn-Sig Kwak (World Journal of Microbiology and Biotechnology, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Reduced brain entropy by repetitive transcranial magnetic stimulation on the left dorsolateral prefrontal cortex in healthy young adults - Donghui Song; Da Chang; Jian Zhang; Wei Peng; Yuanqi Shang; Xin Gao; Ze Wang (Brain Imaging and Behavior, 2019)

Fuzzy time series for real-time flood forecasting - Chang-Shian Chen; You-Da Jhong; Wan-Zhen Wu; Shien-Tsung Chen (Stochastic Environmental Research and Risk Assessment, 2019)

Population pharmacokinetics of oxcarbazepine active metabolite in Chinese paediatric epilepsy patients and its application in individualised dosage regimens - Wei-wei Lin; Xi-wen Li; Zheng Jiao; Jin Zhang; Xin Rao; Da-yong Zeng; Xin-hua Lin; Chang-lian Wang (European Journal of Clinical Pharmacology, 2019)

A comprehensive performance evaluation of heterogeneous Bi2Fe4O9/peroxymonosulfate system for sulfamethoxazole degradation - Wen-Da Oh; Victor W.C. Chang; Teik-Thye Lim (Environmental Science and Pollution Research, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

An ensemble-based likelihood ratio approach for family-based genomic risk prediction - Hui An; Chang-shuai Wei; Oliver Wang; Da-hui Wang; Liang-wen Xu; Qing Lu; Cheng-yin Ye (Journal of Zhejiang University-SCIENCE B, 2018)

Spatial distribution and environmental implications of heavy metals in typical lead (Pb)-zinc (Zn) mine tailings impoundments in Guangdong Province, South China - Tao Chen; Chang Lei; Bo Yan; Li-li Li; Da-mao Xu; Guang-Guo Ying (Environmental Science and Pollution Research, 2018)

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

Stream temperature dynamics in Nam Co basin, southern Tibetan Plateau - Tan-guang Gao; Shi-chang Kang; Ting-jun Zhang; Da-qing Yang; Jian-guo Shang; Xiang Qin (Journal of Mountain Science, 2017)

Contaminant characteristics and environmental risk assessment of heavy metals in the paddy soils from lead (Pb)-zinc (Zn) mining areas in Guangdong Province, South China - Da-Mao Xu; Bo Yan; Tao Chen; Chang Lei; Han-Zhi Lin; Xian-Ming Xiao (Environmental Science and Pollution Research, 2017)

A new hexahydrobenzopyran derivative from the gorgonian-derived Fungus Eutypella sp - Hai-Xia Liao; Da-Wei Sun; Cai-Juan Zheng; Chang-Yun Wang (Natural Product Research, 2017)

Evaluation of the effects of the combination of autologous mesenchymal stem cells and platelet-rich plasma on structural bone allograft healing - Chang-Goo Park; Min Wook Joo; Jinyoung Jeong; Yong-Koo Kang; Da-Reum Lee (Cell and Tissue Banking, 2017)

Antidiarrhoeic effect of Eugenia dysenterica DC (Myrtaceae) leaf essential oil - Maria Raquel Unterkircher Galheigo; Ligia Carolina da Silva Prado; Angélica Martins Moreira Mundin; Dayane Olímpia Gomes; Roberto Chang; Anna Monteiro Correia Lima; Hudson Armando Nunes Canabrava; Luiz Borges Bispo-da-Silva (Natural Product Research, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Cardiac Fas-Dependent and Mitochondria-Dependent Apoptotic Pathways in a Transgenic Mouse Model of Huntington’s Disease - Bor-Tsang Wu; Ming-Chang Chiang; Ching-Yi Tasi; Chia-Hua Kuo; Woei-Cherng Shyu; Chung-Lan Kao; Chih-Yang Huang; Shin-Da Lee (Cardiovascular Toxicology, 2016)

Multiple roles of oxygen in the photoinactivation and dynamic repair of Photosystem II in spinach leaves - Da-Yong Fan; Zi-Piao Ye; Shi-Chang Wang; Wah Soon Chow (Photosynthesis Research, 2016)

Polyhexamethylene guanidine phosphate aerosol particles induce pulmonary inflammatory and fibrotic responses - Ha Ryong Kim; Kyuhong Lee; Chang We Park; Jeong Ah Song; Da Young Shin; Yong Joo Park; Kyu Hyuck Chung (Archives of Toxicology, 2016)

Potential natural exposure of endangered red-crowned crane (Grus japonensis) to mycotoxins aflatoxin B1, deoxynivalenol, zearalenone, T-2 toxin, and ochratoxin A - Da-wei Liu; Hong-yi Liu; Hai-bin Zhang; Ming-chang Cao; Yong Sun; Wen-da Wu; Chang-hu Lu (Journal of Zhejiang University-SCIENCE B, 2016)

The roles of tetrapyrroles in plastid retrograde signaling and tolerance to environmental stresses - Zhong-Wei Zhang; Gong-Chang Zhang; Feng Zhu; Da-Wei Zhang; Shu Yuan (Planta, 2015)

Calcitonin Gene-Related Peptide-Induced Calcium Alginate Gel Combined with Adipose-Derived Stem Cells Differentiating to Osteoblasts - Chang-zhi Huang; Xiao-ning Yang; Da-cheng Liu; Yi-gong Sun; Xing-ming Dai (Cell Biochemistry and Biophysics, 2015)
Calcitonin gene-related peptide (CGRP) has been confirmed with induction osteoblastic differentiation, but if it can make the three-dimensional culture of adipose-derived stem cells (ADSCs) to the osteoblastic differentiation, thus constructing tissue-engineered bone rare reports. To investigate the feasibility of exogenous CGRP-induced calcium alginate gel combined with ADSCs from rabbits in three-dimensional condition to construct tissue-engineered bone. ADSCs were obtained by collagenase I digestion of the subcutaneous adipose tissue of inguinal region of New Zealand rabbits. At the third passage, cells were mixed with sodium alginate to prepare calcium alginate gel, and the cells were assigned into two-group cultivates in 24 orifice plates. ADSCs in the control group were treated with DMEM/F-12 medium supplemented with 10 −2 mol/L β-glycerophosphate sodium, 10 −7 mol/L dexamethasone, 50 mg/L ascorbic acid, 0.1 % volume fraction of fetal bovine serum. ADSCs in the experimental group were incubated with the same medium as above, and in addition 1.5 µg/L CGRP was added. The cells proliferation and the mRNA expressions of collagen I and osteocalcin were detected by MTT and RT-PCR assays, respectively and alkaline phosphatase(ALP)and calcium concentration at different induction time were detected. The cell proliferation curves were S shaped. The OD values of experimental group were higher than those of control group at 1, 3, 5, 7, 14, and 21 days after osteogenic induction ( P < 0.05). ALP and alizarin red stains of ADSCs were all positive, but golden round nodes became bigger and more in the experimental group compared with the control group after 2 weeks. At 7 and 14 days, collagen I and osteocalcin mRNA expression were greater in the experimental group than the control group. ALP and calcium concentration of experimental group were higher than that of control group at 1, 2, 3, 4 weeks after osteogenic induction ( P < 0.05). Thus, these results show that the CGRP-induced ADSCs combined with calcium alginate gel to osteoblasts differentiation.

Genetic analysis and molecular mapping of QTLs associated with resistance to bacterial blight in a rice mutant, SA0423 - Hsin-Yi Tseng; Da-Gin Lin; Hsiao-Ying Hsieh; Ya-June Tseng; Wen-Bin Tseng; Chun-Wei Chen; Chang-Sheng Wang (Euphytica, 2015)

Actinomadura amylolytica sp. nov. and Actinomadura cellulosilytica sp. nov., isolated from geothermally heated soil - Jian-Yu Jiao; Lan Liu; En-Min Zhou; Da-Qiao Wei; Hong Ming; Wen-Dong Xian; Chang-Guo Yuan; Jing-Mei Zhong; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Impact of LPS-Induced Cardiomyoblast Cell Apoptosis Inhibited by Earthworm Extracts - Ping-Chun Li; Yun-Chen Tien; Cecilia Hsuan Day; Peiying Pai; Wei-Wen Kuo; Tung-Sheng Chen; Chia-Hua Kuo; Chang-Hai Tsai; Da-Tong Ju; Chih-Yang Huang (Cardiovascular Toxicology, 2015)

Tree architecture varies with forest succession in evergreen broad-leaved forests in Eastern China - Xiao-Dong Yang; En-Rong Yan; Scott X. Chang; Liang-Jun Da; Xi-Hua Wang (Trees, 2015)

Promoter hypermethylation may be an important mechanism of the transcriptional inactivation of ARRDC3, GATA5, and ELP3 in invasive ductal breast carcinoma - Da Wang; Peng-Na Yang; Jin Chen; Xian-Yao Zhou; Qiu-Jun Liu; Hong-Jiang Li; Chang-Long Li (Molecular and Cellular Biochemistry, 2014)

Ichnofabrics and their environmental interpretation from the fluvial deposits of the Middle Triassic Youfangzhuang Formation in Western Henan, Central China - Min Wang; Yongan Qi; Da Li; Mingyue Dai; Yuguang Chang (Journal of Earth Science, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Porous-grain-upper-boundary model and its application to Tarim Basin carbonates - Yu-Qian Guo; Hong-Da Ma; Kai-Bo Shi; Hong Cao; Lu-Zhong Huang; Feng-Chang Yao; Tian-Yue Hu (Applied Geophysics, 2013)

First Molecular Typing of Cryptococcemia-Causing Cryptococcus in Central-West Brazil - Rosianne Assis de Sousa Tsujisaki; Anamaria Mello Miranda Paniago; Manoel Sebastião da Costa Lima Júnior; Débora de Souza Olartechea de Alencar; Fernanda Luíza Espinosa Spositto; Maína de Oliveira Nunes; Luciana Trilles; Marilene Rodrigues Chang (Mycopathologia, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Optimization of Water Resources Utilization by PSO-GA - Jian-xia Chang; Tao Bai; Qiang Huang; Da-wen Yang (Water Resources Management, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Oral administration of bovine lactoferrin inhibits bacterial infection in tilapia and elevates survival after bacterial infection: an examination of its immune-modulating properties - Yi-Da Wang; Hsiao-Yun Chang; Jyh-Yih Chen; Jian-Chyi Chen (Aquaculture International, 2013)

Effect of dehydroepiandrosterone administration on recovery from mix-type exercise training-induced muscle damage - Yi-Hung Liao; Kun-Fu Liao; Chung-Lan Kao; Chung-Yu Chen; Chih-Yang Huang; Wei-Hsiang Chang; John L. Ivy; Jeffrey R. Bernard; Shin-Da Lee; Chia-Hua Kuo (European Journal of Applied Physiology, 2013)

Changes in physiology and protein abundance in salt-stressed wheat chloroplasts - Abu Hena Mostafa Kamal; Kun Cho; Da-Eun Kim; Nobuyuki Uozumi; Keun-Yook Chung; Sang Young Lee; Jong-Soon Choi; Seong-Woo Cho; Chang-Seob Shin; Sun Hee Woo (Molecular Biology Reports, 2012)

Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) and Neurodegenerative Disorders - Yu-Chang Chen; Jui-Sheng Wu; Hsin-Da Tsai; Chien-Yu Huang; Jin-Jer Chen; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2012)

Lamiolactone, a new iridoid lactone from Lamiophlomis rotata - Jun-Jie Tan; Jun-Ming Tan; Chang-Heng Tan; Shi-Jin Qu; Da-Yuan Zhu (Natural Product Research, 2012)

Erratum to: Fisetin induces apoptosis in human cervical cancer HeLa cells through ERK1/2-mediated activation of caspase-8-/caspase-3-dependent pathway - Tsung-Ho Ying; Shun-Fa Yang; Su-Ju Tsai; Shu-Ching Hsieh; Yi-Chang Huang; Da-Tian Bau; Yi-Hsien Hsieh (Archives of Toxicology, 2012)

Fisetin induces apoptosis in human cervical cancer HeLa cells through ERK1/2-mediated activation of caspase-8-/caspase-3-dependent pathway - Tsung-Ho Ying; Shun-Fa Yang; Su-Ju Tsai; Shu-Ching Hsieh; Yi-Chang Huang; Da-Tian Bau; Yi-Hsien Hsieh (Archives of Toxicology, 2012)

Development of transgenic zooplankton Artemia as a bioreactor to produce exogenous protein - Shih-Hung Chang; Ben-Chang Lee; Yan-Da Chen; Yin-Chou Lee; Huai-Jen Tsai (Transgenic Research, 2011)

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process - In-Chun Wang; Min-Jeong Lee; Da-Young Seo; Hea-Eun Lee; Yongsun Choi; Woo-Sik Kim; Chang-Sam Kim; Myung-Yung Jeong; Guang Jin Choi (AAPS PharmSciTech, 2011)

Combination Efficacy of Voriconazole and Amphotericin B in the Experimental Disease in Immunodeficient Mice Caused by Fluconazole-resistant Cryptococcus neoformans - Eriques Gonçalves Silva; Claudete Rodrigues Paula; Amanda Latercia Tranches Dias; Marilene Rodrigues Chang; Luciana da Silva Ruiz; Valderez Gambale; Renato Araujo Prates; Martha Simões Ribeiro (Mycopathologia, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Erratum to: Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)

Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)

High-frequency somatic embryogenesis from germinated zygotic embryos of Schisandra chinensis and evaluation of the effects of medium strength, sucrose, GA3, and BA on somatic embryo development - Ai Hua Chen; Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Chang Yeon Yu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Anti-apoptotic Actions of PPAR-γ Against Ischemic Stroke - Wen-Hsuan Fong; Hsin-Da Tsai; Yu-Chang Chen; Jui-Sheng Wu; Teng-Nan Lin (Molecular Neurobiology, 2010)

Laboratory study of fluid viscosity induced ultrasonic velocity dispersion in reservoir sandstones - Tao He; Chang-Chun Zou; Fa-Gen Pei; Ke-Ying Ren; Fan-Da Kong; Ge Shi (Applied Geophysics, 2010)

Decreased levels of serum brain-derived neurotrophic factor in drug-naïve first-episode schizophrenia: relationship to clinical phenotypes - Da Chun Chen; Jing Wang; Bo Wang; Sheng Chang Yang; Chong Xi Zhang; You Lan Zheng; Yan Li Li; Ning Wang; Ke Bing Yang; Mei Hong Xiu; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2009)

Adaptation of the externally feeding bug Elasmucha necopinata (Hemiptera: Acanthosomatidae) to its fig host - Guang-Chang Ma; Hao-Yuan Hu; Li-Ming Niu; Yue-Guan Fu; Zheng-Qiang Peng; Wen-Jun Bu; Da-Wei Huang (Symbiosis, 2009)

Two new N -oxide Lycopodium alkaloids from Huperzia serrata - Heng-Bin Wang; Chang-Heng Tan; Jun-Jie Tan; Shi-Jin Qu; Yi-Lei Chen; Yi-Ming Li; Shan-Hao Jiang; Da-Yuan Zhu (Natural Product Research, 2009)

Modified biplanar open-wedge high tibial osteotomy with rigid locking plate to treat varus knee - Hai-ning Zhang; Jie Zhang; Cheng-yu Lv; Ping Leng; Ying-zhen Wang; Xiang-da Wang; Chang-yao Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Interleukin-1β enhances the effect of serum deprivation on rat annular cell apoptosis - Chang-Qing Zhao; Da Liu; Hai Li; Lei-Sheng Jiang; Li-Yang Dai (Apoptosis, 2007)

Calcineurin differentially regulates fast myosin heavy chain genes in oxidative muscle fibre type conversion - Nuno da Costa; Julia Edgar; Peck-Toung Ooi; Yuhong Su; Joachim D. Meissner; Kin-Chow Chang (Cell and Tissue Research, 2007)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Up-regulation interleukin-6 and interleukin-8 by activated protein C in lipopolysaccharide-treated human umbilical vein endothelial cells - Yi Li; Bin Du; Jia-qi Pan; De-chang Chen; Da-wei Liu (Journal of Zhejiang University-SCIENCE B, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Changes in purine content of tilapia surimi products during processing - Shyi-Neng LOU; Hui-Huang CHEN; Po-Yang HSU; Da-Hsuan CHANG (Fisheries Science, 2005)

The use of RAPD markers for detecting genetic diversity, relationship and molecular identification of Chinese elite tea genetic resources [Camellia sinensis (L.) O. Kuntze] preserved in a tea germplasm repository - Liang Chen; Qi-kang Gao; Da-ming Chen; Chang-jie Xu (Biodiversity and Conservation, 2005)

Cluster characterisation and temporal expression of porcine sarcomeric myosin heavy chain genes - Y. M. Sun; N. Da Costa; K. C. Chang (Journal of Muscle Research and Cell Motility, 2003)

Allele-specific differential expression of a common adiponectin gene polymorphism related to obesity - Wei-Shiung Yang; Pei-Ling Tsou; Wei-Jei Lee; Da-Lun Tseng; Chi-Ling Chen; Chi-Chung Peng; Kuan-Ching Lee; Mei-Ju Chen; Chang-Jen Huang; Tong-Yuan Tai; Lee-Ming Chuang (Journal of Molecular Medicine, 2003)

Molecular and quantitative characterisation of the porcine embryonic myosin heavy chain gene - Y. M. Sun; N. da Costa; R. Birrell; A. L. Archibald; H. Alzuherri; K. C. Chang (Journal of Muscle Research and Cell Motility, 2001)

Fresh snow chemistry from high mountain regions in central himalayas - Shi-chang Kang; Da-he Qin; Tan-dong Yao; A. Mayewski Paul; Whitlow Sallie (Chinese Geographical Science, 2000)

The 5′-end of the porcine perinatal myosin heavy chain gene shows alternative splicing and is clustered with repeat elements - Nuno Da Costa; Nicolas Beuzen; Irene Johnston; Christine McGillivray; Yuh-man Sun; Kin Chow Chang (Journal of Muscle Research and Cell Motility, 2000)

Ri-mediated transformation of Artemisia annua with a recombinant farnesyl diphosphate synthase gene for artemisinin production - Da-Hua Chen; Chang-Jun Liu; He-Chun Ye; Guo-Feng Li; Ben-Ye Liu; Yu-Ling Meng; Xiao-Ya Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)